- #1
issacnewton
- 1,041
- 37
- Homework Statement
- Prove that ##n##th Fibanacci number ##F_n## is even if and only if ##3|n##
- Relevant Equations
- Mathematical Induction
Let ##P(n)## be the statement that
$$ F_n \text{ is even} \iff (3 \mid n) $$
Now, my base cases are ##n=1,2,3##. For ##n=1##, statement I have to prove is
$$ F_1 \text{ is even} \iff (3 \mid 1) $$
But since ##F_1 = 1## (Hence ##F_1## not even) and ##3 \nmid 1##, the above statement is vacuously true. Now, for ##n=2##, statement is
$$ F_2 \text{ is even} \iff (3 \mid 2) $$
But, since ##F_2 = 1## (Hence ##F_2## not even) and ##3 \nmid 2##, the above statement is vacuously true. Lastly, for ##n=3##, statement is
$$ F_3 \text{ is even} \iff (3 \mid 3) $$
Since ##F_3=2##, we have ##F_3## as even and ##3 \mid 3 ##. Since both antecedent and consequent are true, the biconditional is true. So, base cases are true. Now, let ## k \geqslant 3## be an arbitrary in ##\mathbb{N}##. And suppose that ##P(m)## is true for ##1 \leqslant m \leqslant k##. i.e.
$$ F_m \text{ is even} \iff (3 \mid m) $$
for ##1 \leqslant m \leqslant k##. I have to prove that ##P(k+1)## is true. I have to prove that
$$ F_{k+1} \text{ is even} \iff (3 \mid k+1) $$
Since this is biconditional statement, I will first prove forward direction
$$ F_{k+1} \text{ is even} \to (3 \mid k+1) $$
Suppose that ##F_{k+1}## is even. Now, ##F_{k+1} = F_k + F_{k-1} = 2 F_{k-1} + F_{k-2}##. Using this, I must have ##F_{k-2}## as even. Since ##k \geqslant 3##, it implies ##1 \leqslant k-2 \leqslant k##. Now, I can use the inductive hypothesis and conclude that ##3 \mid (k-2)##. This means that ##k-2 = 3 \alpha## for some ##\alpha \in \mathbb{Z}##. It follows that ##k +1 = 3 (\alpha + 1)## and ##3 \mid (k+1)##.
This proves the forward direction. Now, I have to prove the reverse direction
$$ (3 \mid k+1) \to F_{k+1} \text{ is even} $$
Suppose ##3 \mid (k+1)##. I will try to prove this with contradiction, so assume the opposite of consequent. Hence suppose that ##F_{k+1}## is odd. Since ##F_{k+1} = 2 F_{k-1} + F_{k-2}##, it must be true that ##F_{k-2}## is odd. As before, since ##1 \leqslant k-2 \leqslant k##, using contrapositive of inductive hypothesis
$$ (F_{k-2} \text{ is odd}) \to (3 \nmid k-2)$$
Hence, it must be true that ##3 \nmid (k-2)##. But, as ##3 \mid (k+1)##, I have ## (k+1) = 3 \alpha## and ##(k-2) = 3(\alpha -1)##. This means that ##3 \mid (k-2)##. But this is a contradiction. So, initial assumption that ##F_{k+1}## is odd, is wrong. Hence ##F_{k+1}## is even. This proves the reverse direction. Hence
$$ F_{k+1} \text{ is even} \iff (3 \mid k+1) $$
So, ##P(k+1)## is true. Using strong induction, this means that ##P(n)## is true for all ##n \in \mathbb{N}##.
Is this a correct proof ?
Thanks ##\smile##
$$ F_n \text{ is even} \iff (3 \mid n) $$
Now, my base cases are ##n=1,2,3##. For ##n=1##, statement I have to prove is
$$ F_1 \text{ is even} \iff (3 \mid 1) $$
But since ##F_1 = 1## (Hence ##F_1## not even) and ##3 \nmid 1##, the above statement is vacuously true. Now, for ##n=2##, statement is
$$ F_2 \text{ is even} \iff (3 \mid 2) $$
But, since ##F_2 = 1## (Hence ##F_2## not even) and ##3 \nmid 2##, the above statement is vacuously true. Lastly, for ##n=3##, statement is
$$ F_3 \text{ is even} \iff (3 \mid 3) $$
Since ##F_3=2##, we have ##F_3## as even and ##3 \mid 3 ##. Since both antecedent and consequent are true, the biconditional is true. So, base cases are true. Now, let ## k \geqslant 3## be an arbitrary in ##\mathbb{N}##. And suppose that ##P(m)## is true for ##1 \leqslant m \leqslant k##. i.e.
$$ F_m \text{ is even} \iff (3 \mid m) $$
for ##1 \leqslant m \leqslant k##. I have to prove that ##P(k+1)## is true. I have to prove that
$$ F_{k+1} \text{ is even} \iff (3 \mid k+1) $$
Since this is biconditional statement, I will first prove forward direction
$$ F_{k+1} \text{ is even} \to (3 \mid k+1) $$
Suppose that ##F_{k+1}## is even. Now, ##F_{k+1} = F_k + F_{k-1} = 2 F_{k-1} + F_{k-2}##. Using this, I must have ##F_{k-2}## as even. Since ##k \geqslant 3##, it implies ##1 \leqslant k-2 \leqslant k##. Now, I can use the inductive hypothesis and conclude that ##3 \mid (k-2)##. This means that ##k-2 = 3 \alpha## for some ##\alpha \in \mathbb{Z}##. It follows that ##k +1 = 3 (\alpha + 1)## and ##3 \mid (k+1)##.
This proves the forward direction. Now, I have to prove the reverse direction
$$ (3 \mid k+1) \to F_{k+1} \text{ is even} $$
Suppose ##3 \mid (k+1)##. I will try to prove this with contradiction, so assume the opposite of consequent. Hence suppose that ##F_{k+1}## is odd. Since ##F_{k+1} = 2 F_{k-1} + F_{k-2}##, it must be true that ##F_{k-2}## is odd. As before, since ##1 \leqslant k-2 \leqslant k##, using contrapositive of inductive hypothesis
$$ (F_{k-2} \text{ is odd}) \to (3 \nmid k-2)$$
Hence, it must be true that ##3 \nmid (k-2)##. But, as ##3 \mid (k+1)##, I have ## (k+1) = 3 \alpha## and ##(k-2) = 3(\alpha -1)##. This means that ##3 \mid (k-2)##. But this is a contradiction. So, initial assumption that ##F_{k+1}## is odd, is wrong. Hence ##F_{k+1}## is even. This proves the reverse direction. Hence
$$ F_{k+1} \text{ is even} \iff (3 \mid k+1) $$
So, ##P(k+1)## is true. Using strong induction, this means that ##P(n)## is true for all ##n \in \mathbb{N}##.
Is this a correct proof ?
Thanks ##\smile##